PEMODELAN ARSITEKTUR SISTEM INFORMASI LAYANAN CUSTOMS, IMMIGRATE DAN QUARANTINE (CIQ) DALAM RANGKA MENCAPAI GOOD GOVERNANCE 4.0 - Fransiskus M H Tjiptabudi (J-Icon : Jurnal Komputer dan Informatika, 2020)
One of the Nawa Cita programs established by the government is to develop Indonesia from the periphery by strengthening human resources, infrastructure and services to be the basis of the government's commitment to develop the East Nusa Tenggara (NTT) region. As a province bordering the Democratic Republic of Timor-Leste, NTT has become a target for the development of border areas, namely the construction of an Integrated Cross-border Post (PLBN) with various supporting facilities. Integrated PLBN is a "home" for CIQ services (Customs / customs, Immigrate / immigration, and Quarantine / quarantine) under the authority of 5 ministries. At present, each service does not yet have an integrated system and does not yet have supporting infrastructure to optimize coordination and collaboration between institutions so that it affects the effectiveness and efficiency of one-stop services. The purpose of this research is to create a cross platform information system architecture model to support business processes carried out by the customs, immigration and quarantine authorities in three (3) Integrated State Border Posts (PLBN) in the NTT region by applying the concept of Enterprise Architecture Planning (EAP). The proposed information system architecture aims to solve the problems encountered in carrying out business processes and services as well as supporting national government policies and strategies in managing border regions between countries. The results of this study are expected to be applied to support the business processes carried out by connecting all relevant institutions in order to realize good governance in the era of the industrial revolution 4.0.